SOFT POWER TIONGKOK DALAM DIPLOMASI DI INDONESIA MELALUI PENGGUNAAN BUDAYA POPULER DONGHUA (ANIMASI TIONGKOK) PADA FILM NE ZHA - Difani, Heldissa; Takwa, Tuah Kalti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
The use of popular culture can be an instrument of soft power has become a common diplomatic practice in international relations, as seen in China’s diplomacy in Indonesia. Diplomacy through popular culture is one of China’s efforts to strengthen its soft power in Indonesia, using Donghua (Chinese animation) as part of its strategy. This study aims to examine how China’s diplomacy utilizes popular culture as part of its strategy to strengthen its soft power influence in Indonesia. This study employs soft power theory and new public diplomacy to analyze China’s efforts to use animated popular culture as a modern cultural element in its soft power diplomacy. The method employed in this study is qualitative, with a literature review as the primary source of analysis. The results of this study indicate that China utilizes Donghua popular culture as part of its “Going Out” Cultural Strategy to strengthen its influence and disseminate Chinese culture in Indonesia. One example is the release of the animated film Ne Zha in Indonesia, which introduces Chinese culture in a modern way. Keywords: Animation, Culture Strategy, Popular Culture, Soft Power, Tiongkok.